Social comparison nudges—Guessing the norm increases charitable giving - Bartke, Simon; Friedl, Andreas; Gelhaar, Felix; Reh, Laura (Economics letters, 2017)
Social comparison nudges that employ descriptive norms were found to increase charitable giving. This paper finds that individuals who receive a descriptive norm donate significantly more when they have to guess the descriptive norm beforehand. We argue that guessing draws attention to the norm and therefore increases its effectiveness. Our results suggest that the effectiveness of nudges that use descriptive norms depends on how the a priori beliefs about the descriptive norm are update
Keywords: Social comparison nudge; Attention; Field experiment; Charitable giving; Social norms